Studi Kesiapan Pt Asuransi Staco Mandiri Menjelang Pemisahan (SPIN OFF) Unit Syariah - Nabhan, Nabhan; Lestari Prasilowati, Sri (GEMA EKONOMI, 2023)
This research aimed to determine the readiness of the Syariah Unit of PT Asuransi Staco Mandiri's readiness to fulfill the spin-off obligations as mandated in the Insurance Law number 40 of 2014, no later than 2024. The research variables consist of equity, contributions, underwriting surplus of tabarru' fund, profit company, and the availability of human resources both quantitatively and qualitatively. This research uses secondary data obtained from research objects plus relevant information from credible sources. The analytical method used is ARIMA and combined with the Double Smoothing Exponential to predict the financial and operational aspects of the Company. The study results show that PT Asuransi Staco Mandiri's Sharia business unit is ready to spin off. However, regarding human resources, it is necessary to carry out efforts and programs that focus on fulfilling them with the remaining time available.